Lectotypifications in Uruguayan Stevia (Asteraceae, Eupatorieae) - Rodríguez-Cravero, Juan F.; Gutiérrez, Diego G.; Katinas, Liliana (Phytotaxa, 2017)
Eleven species of Stevia were reported from Uruguay: S. aristata, S. burkartii, S. cinerascens, S. congesta, S. entreriensis, S. gratioloides, S. multiaristata, S. ophryodonta, S. sabulonis, S. satureiifolia, and S. selloi. Seven are shared with Argentina, five with Brazil, four with Paraguay, and two are endemic to Uruguay. During the revision of these species of Stevia, we detected names which need lectotypifications. As a result of our analysis four lectotypes are designated for names currently accepted in Stevia: S. congesta, S. gratioloides, S. polycephala (= Stevia aristata) and Dissothrix hassleriana (= Stevia entreriensis). We also clarified the original localities of type materials of S. congesta which occurs in Uruguay and, probably, in Brazil.